Otoritas ASEAN Intergovernmental Commission on Human Rights (AICHR) Dalam Skema Prinsip Non- Intervensi - Ismiya, Azizatu; Putri, Penny Kurnia; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
This study aims to determine the authority of ASEAN Intergovernmental Commission on Human Rights (AICHR) as the ASEAN Human Rights Agency in the non-intervention principle scheme using qualitative descriptive research methods. The increasing cases of human rights violations in Southeast Asia has become a question for the existence of AICHR, which was deliberately formed with the aim of tackling the issue of human rights violations. This research concludes that the AICHR's performance authority in handling cases of human rights violations in the region, in fact, must clash with the non-intervention principle scheme of its parent organization, ASEAN. So, in this case, to maximize the performance of AICHR ideally, it is necessary to re-construct the ASEAN Way regime by collaborating the principles of non-intervention and humanitarian intervention in accordance with the development of international norms. Keywords: AICHR, Non-Intervention Principles, Implication, Human Rights.